American Moderns : Bohemian New York and the Creation of a New Century - Stansell, Christine (Book collections on Project MUSE., 2010)
In the early twentieth century, a brand of men and women moved to New York City. For them, the city's immigrant neighborhoods provided a place where the fancies and forms of a new America could be tested. This book tells the story of most famous of these neighborhoods, Greenwich Village, which became a symbol of social and intellectual freedom.